Effect of harvesting methods and post-harvest treatments on storage behaviour of Nagpur mandarin (Citrus reticulata) fruit - SONKAR, P K; LADANIYA, M S; SINGH, SHYAM (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted dJIring 1995-97 to evaluate the harvesting methods, viz snapping (twisting and pulling) and clipping with reference to injuries and shelf-life of Nagpur mandarin during Ambia (spring) and Mrig (monsoon) crop season. Harvesting rate was slightly less in clipping (315 fruits/person/hour) compared with the conventional snapping (350 fruits/person/hour). In snap method of harvesting, 8.79-9.14% fruits were injured at stem end (slight to severe plugging) in Ambia (spring) season indicating economical loss to growers since such fruits are not marketable. In Mrig (monsoon) crop season (1997) harvesting by snap method resulted in negligible (< 1 %) injuries. Injuries due to puncturing by longer stems to adjacent fruits were 0.25 to 0.34% in snap hanvest and 1.72% in clipping. Wax (highshine wax 2.5%) treatment reduced fruit weight loss in storage. The addition of 2,4-D (@ 500 ppm) in wax helped in retaining greeness of pedicel in clipped fruit. Decay was considerably less in clipped fruit and further reduced by fungicidal wax treatment during storage up to 15 days under ambient condition and 45 days under refrigerated condition. The carbendazim (@ 2000 ppm) treatment through wax was ineffective especially in snap harvested fruit (with slight to severe injury) in controlling decay. The total soluble solids content did not change much while titratable acidity dropped more so in snap harvested froit as compared to clipped fruit in storage. Flavour and acceptability score were highest in clipped fruit after storage.